PERAN PRIVATE BRAND STRATEGY UNTUK MENINGKATKAN IMAGE RETAILER - Effendy, Dandy Aditya (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Retail development in Indonesia is growing rapidly with the emergence of new retailers and local retailers. This is why retail creating a Private Label product as a retail flagship product for them. The level of demand for private label products with good quality and optimal price will increase, so it requires the Private Brand Strategy and supplier of private label right in order to create a good image in the eyes of consumers. In general, Private Label products are products manufactured and contracted by the retailer to produce products using the brand name owned retailer. Private labels are expected to continue to evolve to meet customer needs and improve the margins of modern retailers. Conditions of competition between retail companies, plus the threat of entry of new entrants and product / service replacement and increased bargaining power of buyers and suppliers forcing retailers to determine the right strategy to win in the competition. Then the use of Private Brand Strategy used to anticipate the impending threat.